Proliferation Of Unlicensed Mining In Indonesia When The Minerba Law Was Enacted - Sri Suatmiati; Feri Tuispani; Reny Okpirianti (Green Publisher Indonesia, 2022)
Background: Article 33, Section 3 of the 1945 Constitution of the Republic of Indonesia states,